2021
DOI: 10.1177/03000605211040762
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin induces platinum-resistant epithelial ovarian cancer cell apoptosis by targeting SIRT1

Abstract: Objective Previous investigations indicated the anticancer activity of puerarin. The current study aimed to evaluate the effect and molecular mechanisms of puerarin in chemotherapy-resistant ovarian cancer cells. Methods We examined the effects of puerarin in platinum-resistant epithelial ovarian cancer cells in vitro and in vivo. We also analyzed the molecular mechanism underlying Wnt/β-catenin inhibition and sirtuin 1 (SIRT1) regulation following puerarin treatment. Results Our study demonstrated that puerar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…SIRT1 is related to tumor cell proliferation, migration, invasion and angiogenesis [42,43]. A study found that after puerarin treatment of ovarian cancer cells, the expression of SIRT1 decreased and inhibited Wnt/β-catenin signaling pathway, thereby increasing the apoptosis of platinum-resistant ovarian cancer cells [44]. At present, many SIRT1 inhibitors have been reported, and whether puerarin can be used as a SIRT1 inhibitor related to the inhibition of NPC cells remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 is related to tumor cell proliferation, migration, invasion and angiogenesis [42,43]. A study found that after puerarin treatment of ovarian cancer cells, the expression of SIRT1 decreased and inhibited Wnt/β-catenin signaling pathway, thereby increasing the apoptosis of platinum-resistant ovarian cancer cells [44]. At present, many SIRT1 inhibitors have been reported, and whether puerarin can be used as a SIRT1 inhibitor related to the inhibition of NPC cells remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin can inhibit the proliferation and promote apoptosis of bladder cancer T24 cells, and can inactivate NF-κB signaling pathway [15]. Puerarin can also act on liver cancer [16], ovarian cancer [17], cervical cancer [18], esophageal cancer [19], and gastric cancer [20] through different mechanisms. However, there are few studies on puerarin in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Duan et al found that gerberoside effectively inhibited ovarian cancer cell growth in vitro and in vivo by increasing apoptosis. More importantly, it was found that gerberoside decreased SIRT1 expression, thereby attenuating the nuclear accumulation of β-catenin and subsequently inhibiting Wnt/β-catenin signaling, thus sensitizing cisplatin-resistant ovarian cancer cells to chemotherapy [ 64 ]. Miyamoto et al found higher expression of SIRT1 in endometrioid, mucinous, and clear cell carcinomas compared to normal ovarian tissues and follicles, suggesting that high expression of SIRT1 is associated with cisplatin resistance in ovarian cancer cells and is one of the main reasons for poor prognosis in ovarian cancer patients [ 65 ].…”
Section: Effect Of Sirt1 On Premature Ovarian Failure and Ovarian Cancermentioning
confidence: 99%
“…Puerarin, as a natural flavonoid compound isolated from the root of Pueraria lobata, has been shown to have many bioactive functions (anti-inflammatory, antioxidant and antiviral [ 10 ]). Especially, previous studies showed that puerarin has a significant effect on the treatment of inflammatory diseases, such as cancer [ 11 ], diabetes [ 12 ], Alzheimer’s disease [ 13 ] and cardiovascular disease [ 14 ], which evoked the interest of researchers. At present, there are many studies on the anti-inflammatory activity of puerarin.…”
Section: Introductionmentioning
confidence: 99%